2020
DOI: 10.1016/j.xkme.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Associated Collapsing Focal Segmental Glomerulosclerosis: A Report of 2 Cases

Abstract: Collapsing glomerulopathy is an aggressive form of focal segmental glomerulosclerosis with diverse causes. The presence of the apolipoprotein L1 ( APOL1 ) high-risk genotype is a major risk factor for collapsing glomerulopathy in African Americans. Coronavirus disease 2019 (COVID-19) is an emerging pandemic with predominant respiratory manifestations. However, kidney involvement is being frequently noted and is associated with higher mortality. Currently, kidney pathology data for COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 14 publications
5
49
2
1
Order By: Relevance
“…We were able to genotype one Black patient (case 1) who was found to carry the high risk G1/G1 APOL1 genotype. While we did not genotype the other patients in our cohort, 6/7 patients with collapsing glomerulopathy were Black, consistent with other reports demonstrating a strong association between collapsing glomerulopathy in the setting of SARS-CoV-2 infection with high-risk APOL1 genotypes, 17,19,24 a susceptibility that parallels its incidence in HIV-infected patients. 24,25 The last patient with collapsing glomerulopathy (case 6) was a Hispanic patient from Mexico who was also found to have a high risk G2/G2 APOL1 genotype even though the prevalence of homozygous high-risk APOL1 genotypes in mainland Hispanics is 0.1%.…”
Section: Clinical Outcome and Follow Upsupporting
confidence: 90%
See 1 more Smart Citation
“…We were able to genotype one Black patient (case 1) who was found to carry the high risk G1/G1 APOL1 genotype. While we did not genotype the other patients in our cohort, 6/7 patients with collapsing glomerulopathy were Black, consistent with other reports demonstrating a strong association between collapsing glomerulopathy in the setting of SARS-CoV-2 infection with high-risk APOL1 genotypes, 17,19,24 a susceptibility that parallels its incidence in HIV-infected patients. 24,25 The last patient with collapsing glomerulopathy (case 6) was a Hispanic patient from Mexico who was also found to have a high risk G2/G2 APOL1 genotype even though the prevalence of homozygous high-risk APOL1 genotypes in mainland Hispanics is 0.1%.…”
Section: Clinical Outcome and Follow Upsupporting
confidence: 90%
“…The most striking finding is the high incidence of collapsing glomerulopathy (7/17, 41%), which has been reported by multiple groups in association with SARS-CoV-2 infection. [16][17][18][19][20] The mechanism driving this acute glomerular injury process is possibly related to interferon production, a known trigger of collapsing glomerulopathy. [21][22][23] It is less likely that direct podocyte infection is an etiologic factor as the 3/4 patients who were negative for virus by IHC and/or in situ hybridization had podocytopathies (1 each FSGS, collapsing glomerulopathy and minimal change disease).…”
Section: Clinical Outcome and Follow Upmentioning
confidence: 99%
“…In conclusion, the cases detailed in the present report strongly argue in favour of a direct causal link between SARS-CoV-2 infection and the occurrence of CG for which the term COVIDAN can be coined, as a mirror image of HIVAN, as already suggested by Wu et al 9 The cases we report confirm the recently published cases of CG in COVID-19 [7][8][9][10][11]15 and showed that patients homozygous for the APOL1 risk alleles are particularly at risk of developing this complication during the course of COVID-19. Although the long-term renal prognosis for acute renal failure during COVD- 19 is not yet known, the findings of CG among the kidney lesions induced by SARS-CoV-2 suggest that the long-term prognosis to maintain kidney function in individuals with high-risk APOL1 genotype may be far worse, as compared to those in the presence of an isolated, virus-induced, acute tubular necrosis.…”
Section: Discussionsupporting
confidence: 89%
“…Postmortem examinations from China confirmed that SARS-CoV-2 directly infects human kidney tubules and induces acute tubular damage, similar to that observed in our patients, by a direct cytopathic effect and/or the cytotoxic action of CD68 + interstitial macrophages, together with tubular deposition of complement C5b-9. 22 However, unlike Kissling et al 7 and Kadosh et al, 11 but like many others, 7,8,[10][11][12][13][14][15] we were unable to demonstrate the presence of the virus within the podocyte. However, we cannot exclude the possibility that the virus was present below the level of detection.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation